The MKK7-MPK6 MAP Kinase Module Is a Regulator of Meristem Quiescence or Active Growth in Arabidopsis - Dóczi, Róbert; Hatzimasoura, Elizabeth; Farahi Bilooei, Sara; Ahmad, Zaki; Ditengou, Franck Anicet; López-Juez, Enrique; Palme, Klaus; Bögre, László (Frontiers in Plant Science, 2019)
Plant growth flexibly adapts to environmental conditions. Growth initiation itself may be conditional to a suitable environment, while the most common response of plants to adverse conditions is growth inhibition. Most of our understanding about environmental growth inhibition comes from studies on various plant hormones, while less is known about signaling mechanisms involved. The mitogen-activated protein kinase (MAPK) cascades are central signal transduction pathways in all eukaryotes and their roles in plant stress responses is well-established, while increasing evidence points to their involvement in hormonal and developmental processes. Here we show that the MKK7-MPK6 module is a suppressor of meristem activity using genetic approaches. Shoot apical meristem activation during light-induced de-etiolation is accelerated in mpk6 and mkk7 seedlings, whereas constitutive or induced overexpression of MKK7 results in meristem defects or collapse, both in the shoot and the root apical meristems. These results underscore the role of stress-activated MAPK signaling in regulating growth responses at the whole plant level, which may be an important regulatory mechanism underlying the environmental plasticity of plant development.